pTau181 plasma biomarker performance as an inclusion criterion for Alzheimer’s Disease clinical trials - Mammel, Anna; Kumar, Pankaj; Fortna, Ryan; Biehl, Donald; Cruz, Anna; Encarnacion, Mary; Burns, Lindsay H; Kupiec, James; Hsiung, Ging‐Yuek Robin; Mousavi, Ali; MacKenzie, Ian R; Hirsch‐Reinshagen, Veronica; et al. (Alzheimer's & dementia, 2023)
Background Advances in ultrasensitive detection techniques for blood biomarkers allow the quantification of AD‐specific phosphorylated Tau proteins, including Tau phosphorylated at threonine 181 (pTau181) in patient plasma. pTau blood‐based biomarker have shown great promise as inclusion criteria and secondary endpoint evaluation in clinical trials. Method The University of British Columbia (UBC) CARD biobank plasma samples from clinically diagnosed AD and non‐AD patients were used to establish clinical and analytical validity of the pTau181 plasma assay per FDA fit‐for‐purpose guildelines (Neurcode USA, Inc.). We assessed the analytical measurement interval, clinical reportable range, linearity, intra‐laboratory precision, specimen stability, interference, and clinical performance. Result The pTau181 plasma assay provides a robust and accurate biomarker approach for independent determination of AD, with an AUC of 0.9 in our validation study cohort. The cut‐point (≥ 30 ng/L) had 100% sensitivity and 88% specificity for AD diagnosis in autopsy‐confirmed samples. The plasma pTau181 assay appears to be performing well as additional screening metric for inclusion of mild‐to‐moderate AD subjects in Phase 3 clinical trials (i.e. RETHINK‐ALZ and REFOCUS‐ALZ). 89% of the clinical sites participating in the REFOCUS‐ALZ study and 80% of sites participating in the RETHINK‐ALZ had at least 70% of screened subjects meeting this criterion. Conclusion AD plasma biomarker (pTau181) quantified using an RUO assay has great potential both as a diagnostic tool and to streamline clinical trials in AD.